Phytochemistry and antioxidant activity of garcinia prainiana - On, Shamsul; Ahmad, Farediah; Mohd Sirat, Hasnah; Bakhtiar, M. Taher (2011)
Phytochemical investigation of the leaves and stem bark of G. prainiana was carried out. The leaves and stem barks of G. prainiana collected from Kuantan, Pahang were extracted by soxhletextractorwith hexane, dichloromethane and methanol to get the crude exkacts. The crude extracts were purified by column chromatography io yield pure compounds which were characterized spectroscopically using lR, NMR (1D and 2D), UV and MS. Fractionation and purification of the hexane extract of leaves yielded triterpenes, squalene and friedelin. The methanol extract of leaves and stem barks afforded bioflavonoid characterized as morelloflavone and O-methyl fukugetin. Total phenolic content studies were carried out on the crude extracts by using Folin-Ciocalteau reagent. The methanol extract of leaves and stem barks showed the highest total phenolic content expressed as gallic acid and (t)-catechin equivalents. These extracts also showed the highest value of ascorbic acid and butylated hydroxytoluene (BHT) equivalents on forming the phosphomolybdenum complex in the total antioxidant assay. The antioxidant assay on 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical showed that the methanolextract of stem barks had the highest free radical scavenging activity with lCso value 74.5trr9/ml while the isolated compound, morelloflavone revealed a strong free radical scavenging activity with lCsovalue 15.7p9/ml